Dual Access Control for Cloud Storage and Sharing - Sandeep, T.S.; Shreedhara N, Hegde; C., Pui Lin (INTI International University, 2024)
In the field of distributed computing, a significant innovation is now being developed. The process of storing information is extremely difficult for every single person on the planet. Data storage and retrieval can be accomplished in the most straightforward and expedient manner possible through the utilisation of distributed computing. When it comes to distributed computing, security is the most important consideration. An alternative approach to provide access control for distributed computing is what this research workintend to illustrate. Distributed computing can benefit from this design's protective admission control. Additionally, it makes use of a watch and a progressive design in order to facilitate access control, that is more exact. It is possible for us to send, download, and erase papers to and from the fog with ease usingthis method.